Six Sigma adoption in public utilities: a case study. (3rd May 2016) - Prashar, Anupama
Abstract : This paper presents a real-life illustration of a Six Sigma Define–Measure–Analyse–Improve–Control framework blended with innovative tools such as perception analysis, interrelationship diagram, affinity diagram, and Gemba investigation to identify defects and guide process improvements in energy meter-reading in the context of public utilities. The key defects exposed by the analysis of meter-reading data for two months were wrong reading (discrepancy in the data read from the meter), wrong NA (erroneous recording of 'wrong address' status), and wrong PL (erroneous recording of 'premises locked' status). The remedial actions that followed the analysis resulted in a cost saving of INR 0.25 million per annum owing to reduction in the follow-ups for Narela District alone. The study provides a stimulus for the wider application of systematic and data-driven approaches for the measurement and improvement of services.